2021
DOI: 10.1021/acs.jafc.0c07637
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blueberry Anthocyanin-Rich Extracts on Peripheral and Hippocampal Antioxidant Defensiveness: The Analysis of the Serum Fatty Acid Species and Gut Microbiota Profile

Abstract: The current study investigated the positive effects of blueberry anthocyanin-rich extracts (BAE) on either peripheral or hippocampal antioxidant defensiveness and established the connection of the improved antioxidant status with the altered fatty acid species and gut microbiota profile. High-fat diet-induced oxidative stress in C57BL/6 mice was attenuated by BAE administration, which was reflected by strengthened antioxidant enzymes, alleviated hepatic steatosis, and improved hippocampal neuronal status. Seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 40 publications
6
45
0
Order By: Relevance
“…Furthermore, there was a reduced fecal content of SCFAs (Figure 9), which is in line with what has been described in states of prediabetes and diabetes [6,90,97,98]. Regarding the HSuHF animals treated with BJ, the prebiotic properties previously described in other conditions [62,[99][100][101][102] were not replicated in our study. In fact, the reduced abundance of AM found in the HSuHF-treated animals was not prevented, which was accompanied by a significant reduction of Prevotella spp.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, there was a reduced fecal content of SCFAs (Figure 9), which is in line with what has been described in states of prediabetes and diabetes [6,90,97,98]. Regarding the HSuHF animals treated with BJ, the prebiotic properties previously described in other conditions [62,[99][100][101][102] were not replicated in our study. In fact, the reduced abundance of AM found in the HSuHF-treated animals was not prevented, which was accompanied by a significant reduction of Prevotella spp.…”
Section: Discussionsupporting
confidence: 87%
“…The beneficial microbiota activities of anthocyanins are frequently reported in multiple disease animal models and human clinical trials. In C57BL/6 mice, blueberry anthocyanin extract increased Bifidobacterium, Lactobacillus, Roseburia, Faecalibaculum, and Parabacteroides [103]. In the mouse model, bileberry anthocyanins reduced the ratio of Firmicutes/Bacteroidetes (F/B), and increased Akkermansia and Parabacteroides [104].…”
Section: Microbiotamentioning
confidence: 99%
“…For this reason, interest in the biochemistry and biological effects of anthocyanins has increased substantially during the last decade. Several experimental studies have reported that anthocyanins exert a positive impact on health status, as showed by their anti-inflammatory and anti-oxidative effects in a mouse model involving inflammatory bowel disease [ 12 , 13 ], by the regulation of glucose metabolism and insulin, or exerting anti-obesity effects in a mouse model [ 14 , 15 ], inhibiting, in-vitro, the growth of human breast cancer cells [ 16 ]. Concerning CVD, anthocyanins from blueberries or red wine showed improvement in flow-mediated dilation (FMD), and augmentation index in humans, as well as NO-dependent vessel relaxation in mice [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%